EFFECTIVE STRATEGIES FOR DEVELOPING SPEAKING SKILLS IN SECOND LANGUAGE LEARNING - Shaymardonova Farangiz; Tursunova Munira (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores effective methods and strategies for developing speaking skills in second language acquisition. Speaking is considered one of the most important yet challenging skills for language learners. The study highlights the importance of communicative  competence,  interactive  activities,  and  learner-centered  approaches. Both theoretical and practical aspects of teaching speaking are discussed, including the role of motivation, classroom environment, and teacher support. The findings suggest that  consistent  practice,  real-life  communication  tasks,  and  feedback  significantly improve learners' speaking abilities.